The pattern of intrapopulational and interpopulational changes of Betula pendula in Iran, based on leaf morphological traits - Mohammad Esmaeilpour Poodeh; Kambiz Taheri Abkenar; Ali Aalami; Amireslam Bonyad (تاکسونومی و بیوسیستماتیک, 2014)
Despite superior medicinal properties of Birch, there aren’t any studies reported on its morphological diversity. For the first time, leaf samples were collected from four different sites, each site 10 trees and each tree 30 fertile and sterile shoots and leaves (totally 2400). In analyzing the mean values, the Siahmarz kuh showd the maximum and the Marmishoo minimum size mean. Angle of leaf base and number of veins had minimum and fluctuating asymmetry and distance border had a maximum coefficient of variation, minimum and maximum morphological diversity respectively. Average size of sterile leaf traits was larger than average size of fertile leaf traits. It seemed that Siahmarz Kuh is had the most interapopulation diversity and could apply a transition source to sink. The slightest change in the veins of the population in birch was more strongly controlled by genes. Multivariate analyses of variance indicated high statistical significance of all factors: leaf type, population, type population, tree nested population and type × tree nested population. The cluster analysis identified three clusters, the first cluster contained only Marmishoo trees. Because the majority of the population, geographic distribution of genotypes was not consistent with the grouping that could be due to the influence of environmental factors on morphological traits, so it is recommended to use molecular markers. Canonical discriminant analysis showed that petiole length ratio and fluctuating asymmetry could be used in future research on morphological diversity among populations of B. pendula.